HUBUNGAN PERBEDAAN KECERDASAN EMOSIONAL PADA MAHASISWA YANG MENGIKUTI ORGANISASI DENGAN MAHASISWA YANG TIDAK MENGIKUTI ORGANISASI DI UNIVERSITAS BUNDA MULIA - Vicky Vindy; Maria Dwi Yanika Hesti Nugraha (Universitas Bunda Mulia, 2013)
Researchers will conduct research to determine the differences in emotional intelligence in students who join the organization with a student who did not join the organization. The purpose of this study in order to gain more knowledge and insight for both students and colleges. The research method used in this research is descriptive quantitative and perform calculations using SPSS 13.0 for windows. From the research it can be concluded that the hypothesis is acceptable, so there is a significant difference in emotional intelligence in students who join the organization with a student who did not attend the organization. Suggestions that can be applied is the college should require all students to join the organization by providing containers of diverse organizations. Keywords : Emotional Intelligence, Organizations, Student